Sylwia Żółkiewska, Małgorzata Rycharska, Noemi Gryczko: Biznes w świecie mobile. Jak zaprojektować, wykonać i wypromować aplikację mobilną, Warszawa: Wydawnictwo Poltext 2018, 133 [3] s., il. - Sroka, Elżbieta (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The use of mobile applications in cultural institutions is increasingly observed. These issues are discussed in the book by Sylwia Zolkiewska, Malgorzata Rycharska and Noemi Gryczko Business in a Mobile World. How to design, make and promote a mobile application - nominated for the Economicus 2018 award. The publication, published by the Poltext publishing house, is in guidebook form with a large number of footnotes to contemporary literature and recent reports. However, the bibliography at the end of the book is missing. The authors of the publication Business in a Mobile World. How to design, make and promote a mobile application introduce the reader step by step to the entire process of developing, designing and implementing a mobile application. The book consists of ten logically organized chapters and an introduction and conclusion. In addition, it contains numerous graphics and tables to organize the information. The reviewed publication is a valuable and important book on the market in the field of mobile product design. It presents reliable knowledge, taking into account various ways of solving problems that arise during the design of a mobile application. The material collected in the publication can serve a wide range of readers, including entrepreneurs, professionals working on mobile services and products projects, both in terms of UX, information architecture, marketing, project management. In addition, the book can also serve as a compendium of knowledge for professionals studying the design and implementation of a mobile application or game.